New regulation on medical devices made of substances: Opportunities and challenges for pharmacological and toxicological research - Fimognari, Carmela; Barrajón-Catalán, Enrique; Luceri, Cristina; Turrini, Eleonora; Raschi, Emanuel; Bigagli, Elisabetta (Frontiers in Drug Safety and Regulation, 2022)
The Medical Device (MD) Regulation EU 2017/745 (MDR) has provided a completely new and more robust regulatory framework at guarantee of the safety and efficacy of therapeutic options accessing the market. At the same time, the MDR poses several challenges for stakeholders, among which, the most significant lying on MDs made of substances (MDMS) whose mechanism of action should be non-pharmacological, immunological, or metabolic. Moving from single active substances to very complex mixtures, such as the case of natural products, the demonstration of the non-targeted, non-pharmacological mechanism, is even much more challenging since it is very hard to specifically identify and characterize all the interactions each constituent can have within the body. New scientific paradigms to investigate these multiple interactions and delineate the principal mechanism of action through which the effect is achieved are necessary for the correct regulatory classification and placement in the market of MDMS. This article will discuss the difficulties in delineating the boundaries between pharmacological and non-pharmacological mechanisms, practical approaches to the study of complex mixtures and the challenges on the application of current experimental paradigms to the study of the mechanism of action of MDMS.